Synthesis and application of nano-Al2O3 powder for the reclamation of hexavalent chromium from aqueous solutions - Sharma Y.C.; Srivastava V.; Mukherjee A.K. (My University, 2025)
The application of nano-Al2O3 for the removal of hexavalent chromium has been investigated. The nano-Al2O3 was used as an adsorbent in the present study. Nano-alumina was prepared in the laboratory by a sol-gel method. The effect of initial concentration on the removal of Cr(VI) was studied by varying the initial concentration of Cr(VI) from (0.03 to 0.19) mmol•L-1. It was found that the percent removal of Cr(VI) decreases by increasing the initial adsorbate concentration. A contact time of 60 min was found to be sufficient for maximum removal and was recorded as the equilibration time. Resultant data were analyzed by pseudofirst- and pseudosecond-order rate equations. The pH of the solutions affected the removal of Cr(VI) significantly, and removal decreased from (92.2 to 60.8) % by varying the pH from the acidic to alkaline range. Maximum removal was, however, achieved at pH 2.0. It was found that removal decreased by increasing the temperature from (25 to 45) °C. The value of activation energy was very low which indicates that adsorption was physical adsorption. Resulting data at different temperatures were analyzed by the Langmuir and Freundlich equations using linearized equations. Values of different thermodynamic parameters were determined for the resultant data. Values of ΔG°, ΔH°, and ΔS° were calculated and found to be -4.81 kJ•mol-1, -24.28 kJ•mol-1, and -97.57 kJ•mol-1•K -1 at 25 °C at an initial chromium concentration of 0.03 mmol•L-1. Findings of the present study revealed that nano-Al2O3 can be an effective adsorbent for the removal of Cr(VI) from aqueous solutions. This study may serve as baseline data and may help in designing wastewater treatment plants for the treatment of Cr(VI) in particular and that for pollutant species in general. © 2010 American Chemical Society.